Heavy metal concentration (Copper, Manganese and Nickel) in the fish Sarotherodon melanotheron from Alaro stream in Ibadan (2014)
An assessment was carried out on the heavy metal concentration in the organs of the fish Sarotherodon melanotheron from Alaro stream in Ibadan. Fish were collected between January to December 2003 representing both the dry and rainy seasons. Muscle, liver, bone, gills, gut and fins were analyzed for copper (Cu), manganese (Mn) and nickel (Ni) using the inductively coupled plasma-mass spectrometer (ICP-MS).Quality assurance of the results was ensured through the use of bovine liver from the National Institute of Standards and Technology (NIST) as a standard reference material. The range of Cu, Mn and Ni in the fish organs was 4.24-77.79ppm, 13.8-96.5ppm and 0.04-0.92ppm respectively. Mean concentration of Mn in all the organs exceeded the FEPA (Federal Environmental Protection Agency) guideline limits set for it while that of Ni concentration in the muscle was below the WHO standard while all the other organs exceeded it. The heavy metal Cu, apart from the muscle, bone and gills, all the other organs exceeded the WHO recommended limit standard. The study shows that Alaro stream is polluted and fish (S.melanotheron) caught from it is unfit for human consumption due to public health consequences posed in the high concentration of the heavy metals Cu, Mn and Ni.